the introduction of common law: mengenal hukum adat - Reka putri (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2024)
Indonesia is a country with various cultures that dominate each of its people, they firmly adhere to the motto of unity in order to prioritize a sense of tolerance and mutual protection between communities. Indonesian people have unique characteristics in solving problems in every polemic between them, originating from their ancestors, they have strong beliefs in solving problems in their society. Customary law also has an important influence on the continuity of the law we know today, by prioritizing the values upheld by indigenous peoples, even customary law is known as original law. Therefore, the author wants to conduct research with the formulation of the problem of how the role of customary law for national law and how to protect customary law and indigenous peoples.